A new look at hybrid power converter - Arvind Suriya Kumar (Nanyang Technological University, 2021)
Renewable energy has been gaining its significance widely as an alternative energy/power source due to the constant degradation of traditional energy sources. Among them, wind and solar are the two most common sources that provide clean and cost-effective alternatives compared to conservative power generation for applications such as standalone load or grid interconnection systems. Even though renewable energy is evaluated as modern technology for producing electrical energy, the intermittent nature of each energy source is considered to be intricate concerning capital cost and energy production. Therefore, it is recommended to combine both sources to create hybrid renewable energy sources that generate power to the required system where power electronics would play an integral part in the overall design application. Hence, this project aims to model and simulate an integrated wind/solar converter fed to an alternating current (AC) load application which is in the form of a resistive load. Moreover, the influence of power electronics and control systems that are being utilized in the design will be analyzed with the help of simulator packages such as PSIM and MATLAB/SIMULINK.